2021
DOI: 10.3389/fonc.2021.737982
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiotherapy Is Not a Better Alternative to Whole Breast Radiotherapy as a Therapeutic Option for Early-Stage Breast Cancer

Abstract: ObjectiveIntraoperative radiotherapy (IORT) in early-stage breast cancer has been studied over the years. However, it has not been demonstrated whether IORT is more suitable as a therapeutic option for early-stage breast cancer than whole breast radiotherapy (WBRT). Therefore, we performed a meta-analysis to compare the efficacy and safety of IORT to those of WBRT as therapeutic options for early-stage breast cancer patients receiving breast-conserving surgery (INPLASY2020120008).MethodsPubMed, Embase, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
2
6
1
Order By: Relevance
“…Our results align with the findings of previous studies, as we also observed a higher rate of local recurrence in the IORT group compared to the EBRT group. 40 , 42 , 43 Contrary to previous studies, our findings revealed a higher incidence of regional recurrence in the IORT group compared to the EBRT group. 14 , 44 Several factors may contribute to these variations, such as the sample size of our study and the limited occurrence of recurrence within our study population.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results align with the findings of previous studies, as we also observed a higher rate of local recurrence in the IORT group compared to the EBRT group. 40 , 42 , 43 Contrary to previous studies, our findings revealed a higher incidence of regional recurrence in the IORT group compared to the EBRT group. 14 , 44 Several factors may contribute to these variations, such as the sample size of our study and the limited occurrence of recurrence within our study population.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found no statistically significant difference in recurrence‐free survival and overall survival rates between two groups of patients who received either IORT or EBRT 39–41 . These findings are consistent with a substantial body of previous research, including a meta‐analysis by Wang et al, which also failed to demonstrate a meaningful difference between the two treatment modalities in terms of recurrence‐free survival and overall survival.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a more recent meta-analysis, there were concerns regarding the high local recurrence risk associated with IORT, however, compared to WBR, overall survival, recurrence-free survival, distant metastasis-free survival, and cancer-specific survival was not significantly different. Therefore a proper patient selection strategy should always be applied to identify suitable candidates with a lower risk of local recurrence for IORT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with other studies [ 32 34 ]. In a meta-analysis by Wang et al, the risk of skin toxicity was reported significantly lower in the IORT group, however, fat toxicity incident was 3.106 times higher compared to the WBR group [ 21 ]. In the report of the late side-effects and cosmetic outcomes of the phase III GEC-ESTRO trial, The risk of developing symptomatic fat necrosis in 5 years did not differ between APBI and WBR groups.…”
Section: Discussionmentioning
confidence: 99%